Enzyme encapsulation by protein cages. Issue 22 (1st April 2020) - Chakraborti, Soumyananda; Lin, Ting-Yu; Glatt, Sebastian; Heddle, Jonathan G.
Abstract : Protein cages are useful nanometric containers which can capture and encapsulate enzymes via several different approaches. Abstract : Protein cages are hollow protein shells with a nanometric cavity that can be filled with useful materials. The encapsulating nature of the cages means that they are particularly attractive for loading with biological macromolecules, affording the guests protection in conditions where they may be degraded. Given the importance of proteins in both industrial and all cellular processes, encapsulation of functional protein cargoes, particularly enzymes, are of high interest both for in vivo diagnostic and therapeutic use as well as for ex vivo applications. Increasing knowledge of protein cage structures at high resolution along with recent advances in producing artificial protein cages means that they can now be designed with various attachment chemistries on their internal surfaces – a useful tool for cargo capture. Here we review the different available attachment strategies that have recently been successfully demonstrated for enzyme encapsulation in protein cages and consider their future potential.